(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
This article consists of a meta-research on educational reforms. Thus, a research on research on the aforementioned theme within the field of Educational Policy in Brazil is analyzed. The highlighted discussions on educational reform stem from a Doctoral dissertation in Education, whose main purpose was to investigate the epistemologies applied in the study of educational reform from the Epistemological Approach of Education Policy. The research used as main indicators: the number of publications per journal; the year of publication; the institutional origin and location of the authors of the articles; the type of institutional link; thematization; the type of research and its scope; the analysis context; the epistemological perspectives; the reference authors and main concepts. Empirical data derive from scientific articles Qualis A (Education), from which the multiple theoretical-epistemological perspectives chosen by researchers in the investigation of educational reform were apprehended. The analyzes reveal the prevalence of a methodological pluralism or a combined theorization in the investigation of educational reform, with a significant recurrence of the use of theories classified as Marxist or neo-Marxist. Keywords: Educational reform. Meta-research. Epistemologies.